PERSPEKTIF HUKUM SEBAGAI LANDASAN PEMBANGUNAN EKONOMI DI INDONESIA (SEBUAH PENDEKATAN FILSAFAT) - Zulfi Diane Zaini (Jurnal Hukum, 2012)
The role of law in economic development of a nation is something that cannot be ignored its existence. So it is very obvious, if the law of a nation is effective, economic development would be easy to implement. But otherwise if the law has not effective function, it can definitely be an adverse impact on economic development. This condition also exists to Indonesia as a country which is still developing the economic area. Moreover, when Indonesia declared in its constitution as a legal state (rechtstaat). From this it is also implied that Indonesia wants two things: Firstly, the law is expected to function, and secondly, the law can serve, then economic development would be easy to be realized.The economic nationalism spirit in the globalization era shows increasing realization of the urgency to be the national economy which is strong, tough and independent. Economic Democracy is based on the popular and family, as well as cooperative efforts animates economic behavior of individuals and communities. Thus Indonesia Economic Law in the form of the Margin of Appreciation becomes benchmark for the justification of the legal norms which is enforced so the core values of Pancasila as the national ideology is kinship with the community life ideal form in society, is society kinship, so in the field of economics, Pancasila ideology wants kinship (familial Economic Democracy Article 33 of the 1945 Constitution), which is realized through the welfare state.Keywords: Law, Basis, Economic